The architecture of the Iron Age II fortified settlement at Muweilah (Sharjah, United Arab Emirates). (May 2018) - Karacic, Steven; Händel, Marc; Hammer, Emily; Magee, Peter
Abstract : Excavations at Muweilah have uncovered twelve buildings encircled by two pairs of walls and ditches. We have published preliminary studies of several buildings. Research has now progressed to a stage where it is possible to produce a more complete analysis of the architecture. In this report, we present a detailed discussion of the fortifications and each building with its installations. Our assessment of the architecture identified the repeated combination of three rooms in many of the buildings in the Central Area of Muweilah. Moreover, a detailed study of the fortifications revealed several means of accessing Building II, the columned hall, in the Western Area. These findings offer insights into the organisation of Iron Age II settlements in south‐eastern Arabia.